EVOLUTION OF ECONOMIC AND SOCIAL INDICATORS OF RURAL AREAS IN ROMANIA - Iulia Bianca BOGOS; Cristina Maria STERIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In recent decades. rural areas have been facing numerous problems. such as an ageing population. lack of jobs, migration of young people, poor infrastructure which negatively affect the quality of life of rural inhabitants. The aim of the study is to observe the economic and social evolution of the Romanian countryside over the last 10 years, taking into account the disruptive phenomena that have occurred during this period. The study is based on a quantitative and qualitative analysis of data provided by the National Institute of Statistics. In both urban and rural areas, the population tends to decline. In the case of the urban population. there was a 4.09% decrease over the period analyse, from 10.9 million to 10.46 million inhabitants. In contrast, the rural population decreased by 4.57% during the period, from 9.3 million to 8.87 million. Among the main reasons for this decrease, we can mention the high mortality rate (high degree of ageing). but also the migration of the population to Western European countries. a phenomenon that was accentuated with Romania's accession to the European Union in 2007.